In vitro growth response to bacterial wilt pathogen of banana (var. lakatan, Musa acuminata Colla) plantlets regenerated from ethyl methanesulfonate-treated shoot explants - Abello, Nonna Fatima H.; Nuñez, Tessie C. (Annals of Tropical Research, 2019)
Bacterial wilt caused by Ralstonia solanacearum leads to death of infected suckers and reduces the yield of commercially important banana varieties like Lakatan. Among the many varieties of banana, no germplasm with bacterial wilt resistance has been identified yet (Tripathi et al 2004). Mutation induction in plants to develop disease resistance genes using physical or chemical mutagens has been used as alternative to harmful pesticides. To induce mutation for the possible development of resistance to bacterial wilt, shoot tips of Stage 2 in vitro-grown Lakatan plantlets were exposed to 0.1% and 0.2% ethyl methanesulfonate (EMS) for 12 and 24h. Treated and untreated explants were cultured in-vitro to regenerate plantlets. Shoots emerged two days after in vitro inoculation of explants treated with – 0.1% EMS for 12h. Significantly longer shoots also developed from the cultures compared to the untreated explants. The other explants exposed to other treatments had shoot emergence one to three days later. Falcate, curled, irregularly-shaped, and yellowish leaves and pseudostems also developed in EMS-treated cultures. Untreated plantlets exhibited at least one bacterial wilt symptom such as leaf spots, necrosis at pseudostem base, and death six days from the introduction of Ralstonia solanacearum in vitro. Plantlets from explants exposed to 0.1% EMS for 12h did not exhibit disease symptoms even after ten days of exposure to the pathogen and had 100% survival. Seventy one percent of plantlets from explants exposed to 0.1% EMS for 24h and 55% from explants treated with 0.2% EMS for 24h also survived without infection. The surviving plantlets need to be studied further for their ex vitro responses to the pathogen and determine possible genetic changes due to the chemical mutagen treatment.